Analysis of the attributes to decision-making process of the urban freight vehicle choice for Brazilian scenario. (30th March 2020) - Batista, Larissa Almeida Matias De Lima; Rocha, Lara Braide; Bertoncini, Bruno Vieira; Oliveira, Leise Kelli De
The largest cities in Brazil are experiencing a crisis in their urban mobility model. It increases the complexity of the urban distribution process, which requires a considerable effort in decisions such as vehicular choice for urban freight transport. Some attributes might influence the commercial vehicle choice by the decision makers, and they may be related to aspects of the vehicle, the cargo, the delivery area, the freight vehicle restrictions and the requirements from the operation. Recognising this challenge, the key attributes that influence the urban freight vehicle choice were identified through a systematic literature review and their adherence to the Brazilian reality was evaluated through a survey. Also, a stated preference survey was carried out to measure the relationship between decisions on the choice of commercial vehicular mode and the main attributes in this process. The results could support urban transport planners in the development of effective public policies.